Pengaruh Parameter Kimia Terhadap Parameter Biologi Pada Kualitas Air Kolam Pulokerto, Kabupaten Pasuruan - Yudana, IGP Gede Rumayasa; jayanti, shara (Politeknik Kelautan dan Perikanan Bitung, 2023)
The bad water quality is caused by many people managing waste poorly, which can pollute the environment and groundwater sources and create a negative impact on the balance of the ecosystem and surrounding waters. The quality of the water used as a cultivation medium in both columns and ponds is very important to know. This research was conducted to determine the effect of chemical parameters and biological parameters on water quality in the Pulokerto pond, Pasuruan Regency. Water quality measurements were carried out in 3 places, namely plot 13, plot 14 and SB. The chemical parameters tested were nitrite, phosphate, ammonium, Ca, Mg, TOM and alkalinity based on total (CO32- and HCO3-). The biological parameters tested were plankton abundance, TBC (Total Bacteria Count) and TVC (Total Vibrio Count). The results of water quality testing in plot 13 contained high levels of Blue Green Algae at DOC 34, namely 29 cells/ml and in plot SB at DOC 34 it was 22.9 cells/ml and at DOC 59 it was 17.26 cells/ml. Based on the results of the analysis of the quality values of chemical and biological parameters, it can be concluded that chemical parameters do not really influence the biological parameters of water quality in the Pulokerto pond, but rather the results of chemical water quality parameters such as nitrite content, hardness (Ca and Mg) and TOM of P.13 at the time of The 34th Shrimp DOC exceeds the 2014 SNI standard, causing an increase in the number of Blue Green Algae (BGA) which has toxic effects. The number of BGAs exceeded the standard number, namely 29 cells/ml, and on P.13, the 58th DOC showed that the results of green colonies on TVC (Total Vibrio Count) exceeded the standard, namely 200 cells/ml. Green vibrio colonies are a characteristic of the Vibrio parahaemolyticus species which has a poison that is dangerous for fish and shrimp.